Meso-level institutional and journal related indices for Malaysian engineering research - Tahira, M. (Springer Netherlands, 2016)
The literature considers a journal’s h-index as a compared measure, however the relation between institutional level h-index (IHI) and journal related indices (JRI) has not been explored in previous studies at meso-level research assessment. This study applies the scientometric approach to meso-level data to examine the association, functional relationship and correlation analysis to evaluate the reliability of IHI with respect to JRI. For this purpose, data from the Web of Science, journal citation report and time cited features were used. The unit of analysis was Malaysian engineering research with a wider time span of 10 year’s data (2001–2010) and a larger set of journals (1381). We explored the inter-correlation of IHI with a set of eight JRI and applied principle component analysis, regression analysis, and correlation. At the institutional level, the component analysis and functional relationship of the cumulative impact factor and 5 years IF yielded a more strong association with IHI. Cumulative impact factor is a strong predictor for IHI followed by cumulative 5 years impact factor. Correlation matrix results show that average impact factor (AIF) is correlated with immediacy index and Eigenfactor only. AIF and median impact factor (MIF) have no correlation with each other and IHI is correlated with all indices except AIF and MIF. This study puts forward a better understanding in considering new impact indices at meso level for performance evaluation purpose.